The relationship between menarche age and height of adolescent girls in Simpang Kanan sub-district, Aceh Singkil District in 2024 - Laila Apriani Hasanah Harahap; Wardah Iskandar; Meutia Paradhiba; SitiMaisyaroh Fitri Siregar (International Journal of Health and Social Behavior, 2025)
an important biological sign of pubertal development in girls. The height of adolescent girls can also be affected by early menarche. Adolescent girls are an important investment in the country, as they are the next generation that will shape the future. The progress of the nation is determined by the role of active young women in the family, community, and country. They will be the key to creating positive changes and achieving development goals. This study aimed to evaluate the relationship between the nutritional status of adolescent girls and age at onset of menarche. This cross-sectional observational study included 70 adolescent girls aged 17-20 years.